Magnitude of Hypocalcemia in Hypoxic Ischemic Encephalopathy in Term Neonates - Khattak, Noor Ul Haram; Khaliq, Abdul; Khattak, Noor Ul Saba; Gul, Haji (Biological and Clinical Sciences Research Journal, 2025)
Hypoxic ischemic encephalopathy has continued to be a global problem for term neonates and the leading cause of hypocalcemia. Objective: The aim of this study was to find out the magnitude of hypocalcemia in hypoxic ischemic encephalopathy in term neonates. Method: The current study was carried out in neonatal intensive care unit Bacha Khan Medical Complex Gajju Khan Medical College Swabi from August 2023 to January 2024 after taking approval from the ethical committee of the institute. All neonates (from birth to 3 days of age) presented to NICU with hypoxic ischemic encephalopathy were screened for hypocalcaemia. 5 ml venous blood sample was drawn from each participant for serum calcium (total ionized). Cobas Roche analyzer was used to measure total calcium, and an apparatus known as Easylyte was used to measure ionized calcium. Data was analyzed through SPSS. Mean & SD had been derived for age. Post stratification chi square analysis was done and relationship of hypocalcaemia was evaluated with factors such as: ages, weight, sex, gestational age & mother’s educational status. P-value ≤0.05 was deemed as significant. Results: In the current study a total of 120 neonates with hypoxic ischemic encephalopathy were included out of which 80 (66.6%) were male and 40 (33.3%) were females. The mean age of the study population was 1.0-0.7 days. Based on the medical records, the neonate's mean birth weight was 2.85 + 0.6 kg. Serum ionized calcium levels were 4.2 + 0.8 mg/dl on average. The operational definition of hypocalcemia states that it was observed in 41 (34.1%) of participants. The prevalence of hypocalcemia varied significantly among these factors according to the neonate's age at birth, weight at birth, and mothers' educational status (p-value <0.05). Conclusion: Our study concluded that one of the major causes of hypocalcemia (34%) in term neonates is hypoxic ischemic encephalopathy.